Long-term docosahexaenoic acid (DHA) supplementation in cystic fibrosis patients: a randomized, multi-center, double-blind, placebo-controlled trial. (November 2020) - López-Neyra, Alejandro; Suárez, Lucrecia; Muñoz, Marta; de Blas, Ana; Ruiz de Valbuena, Marta; Garriga, María; Calvo, Joaquim; Ribes, Carmen; Girón Moreno, Rosa; Máiz, Luis; González, David; Bousoño, Carlos; et al.
HIGHLIGTHS: Inflammation has a key role in cystic fibrosis pathophysiology Benefits of docosahexaenoic acid (DHA) in cystic fibrosis inflammation are controversial Long-term supplementation with DHA in CF did not improve inflammatory biomarkers Long-term supplementation with DHA in CF did not improve clinical outcomes ABSTRACT: Background: Cystic fibrosis (CF) patients have an alteration in fatty acid (FA) metabolism, associated with increased omega-6 and low omega-3 FA. Previous studies on supplementation with omega-3 FA in CF had contradictory results, and to date there is no evidence to recommend routine use of omega-3 supplements in CF patients. We hypothesized that long-term supplementation with docosahexaenoic acid (DHA) will have beneficial effects in these patients, by reducing pulmonary, systemic and intestinal inflammation. Methods: This was a randomized, double-blind, parallel, placebo-controlled trial. CF patients (age >2 months) were randomized to receive a seaweed DHA oil solution (50 mg/Kg/day) or matching placebo for 48 weeks. Primary outcomes were pulmonary (interleukin [IL]-8), systemic (IL-8) and intestinal (calprotectin) inflammatory biomarkers. Secondary outcomes included other pulmonary (IL-1β, IL-6, neutrophil elastase, lactate and calprotectin) and systemic (serum-IL-1β, IL-6) inflammatory biomarkers, as well as clinical outcomes (FEV1, pulmonary exacerbations, antibiotic use, nutritional status and quality of life). Results: Ninety six CF patients, 44 female, age 14.6±11.9 years (48 DHA and 48 placebo) were included. At trial completion, there were no differences in all primary outcomes [serum-IL-8 (p=0.909), respiratory-IL-8 (p=0.384) or fecal calprotectin (p=0.948)], all secondary inflammatory biomarkers, or in any of the clinical outcomes evaluated. There were few adverse events, with similar incidence in both study groups. Conclusion: In this study, long-term DHA supplementation in CF patients was safe, but did not offer any benefit on inflammatory biomarkers, or in clinical outcomes compared with placebo. (NCT01783613)